2021
DOI: 10.1038/s41598-021-81774-8
|View full text |Cite
|
Sign up to set email alerts
|

Pericytes contribute to the islet basement membranes to promote beta-cell gene expression

Abstract: Abstractβ-Cells depend on the islet basement membrane (BM). While some islet BM components are produced by endothelial cells (ECs), the source of others remains unknown. Pancreatic pericytes directly support β-cells through mostly unidentified secreted factors. Thus, we hypothesized that pericytes regulate β-cells through the production of BM components. Here, we show that pericytes produce multiple components of the mouse pancreatic and islet interstitial and BM matrices. Several of the pericyte-produced ECM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Endothelial cells are responsible for the synthesis and maintenance of the ECM/ basement membrane, specifically producing laminin and collagen IV (25,75,76). Pancreatic pericytes also produce an array of basement membrane components, including collagen IV, laminins, proteoglycans, and nidogen (77). In particular, pancreatic pericytes and endothelial cells both produce laminin a4, which promotes the expression levels of the b-cell genes Ins1, MafA, and Glut2, as well as GSIS (77).…”
Section: Interactions Of B-cells With the Basement Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial cells are responsible for the synthesis and maintenance of the ECM/ basement membrane, specifically producing laminin and collagen IV (25,75,76). Pancreatic pericytes also produce an array of basement membrane components, including collagen IV, laminins, proteoglycans, and nidogen (77). In particular, pancreatic pericytes and endothelial cells both produce laminin a4, which promotes the expression levels of the b-cell genes Ins1, MafA, and Glut2, as well as GSIS (77).…”
Section: Interactions Of B-cells With the Basement Membranementioning
confidence: 99%
“…Pancreatic pericytes also produce an array of basement membrane components, including collagen IV, laminins, proteoglycans, and nidogen (77). In particular, pancreatic pericytes and endothelial cells both produce laminin a4, which promotes the expression levels of the b-cell genes Ins1, MafA, and Glut2, as well as GSIS (77).…”
Section: Interactions Of B-cells With the Basement Membranementioning
confidence: 99%
“…Furthermore, ex vivo reconstitution experiments with both pericytes and pericyte conditioned media, demonstrated that pericytes were able to stimulate beta cell proliferation. These studies also implicated vascular basement membrane components that are produced by pericytes as important beta cell pro-proliferative molecules [29]. Many additional studies have gone on to explore the role of ECM and vasculature components in promoting proliferation in the neonatal islet and are reviewed extensively in [30,31].…”
Section: Establishment Of Beta Cell Massmentioning
confidence: 99%
“…S1.4). We similarly noted cluster-enriched expression of endosialin/CD248 molecule a (cd248a), forkhead box c1b (foxc1b), melanoma cell adhesion molecule b (mcamb), and laminin b1b (lamb1b), orthologs of which are expressed in mouse pericytes (Bagley et al, 2008;Middleton et al, 2005;Sakhneny et al, 2021;Siegenthaler et al, 2013), Fig. 1B, Table S1.4).…”
Section: Resultsmentioning
confidence: 71%
“…Moreover, mouse orthologs for half of the ten most enriched genes in this cluster (ranked by log 2 fold change, adj.p<0.05; Table S1.4 ) are expressed in pericytes, including duplicates of regulator of G protein signaling 5 ( rgs5a and rgs5b ), endothelin receptor type Aa ( ednraa ), and nidogen 1b ( nid1b ; Fig. 1B, Table S1.4 ; (Bondjers et al, 2003; Kitazawa et al, 2011; Sakhneny et al, 2021)). Other significantly enriched genes (log 2 fold change>0.75, adjp<0.05) included notch3 , which is expressed in zebrafish brain pericytes (Wang et al, 2014) and potassium inwardly rectifying channel subfamily J member 8 ( kcnj8 ), a marker of mouse brain pericytes ((Bondjers et al, 2006), Fig.…”
Section: Resultsmentioning
confidence: 99%